VD_FINDINFO ML / 2013 / 273 vom 17. Dezember 2013 - VD Tribunal cantonal (2013)
MEILLEURE FORTUNE, FÉRIES DE POURSUITE, CALCUL DU DÉLAI, OBSERVATION DU DÉLAI | 265a al. 1 LP, 239 al. 1 CPC (CH), 321 al. 2 CPC (CH)